Nature of Logarithmic Function : Look at the following two sets of examples 1st set: 23 = 8 ? log2 8 = 3 24 = 16 ? log2 16 = 4 25 = 32 ?

log2 32 = 5 Here as the number (8, 16, 32) increases,the log of the number (3, 4, 5) increas es. Note that the base (2) is more than 1. What is seen to be true here in this example, is in fact true in general. The general statement is If a > 1, n1 > n2 ? loga n1 > loga n2 i.e. when the base is more than 1, the logarithm function is an increasing funct ion. 2nd set: (1/2)5 = 1/32 ? log(1/2) (1/32) = 5 (1/2)4 = 1/16 ? log(1/2) (1/16) = 4 (1/2)3 = 1/8 ? log(1/2) (1/8) = 3 Here as the number (1/32, 1/16, 1/8) increases,the logarithm of the number (5, 4 , 3) decreases. Note that the base (1/2) is less than 1. What is seen to be true here in this example, is infact true in general. The general statement is If 0 < a < 1, n1 > n2 ? loga n1 < loga n2 i.e. when the base is less than 1 (and positive), the logarithm function is a decreasing function. Solved Example 1 of Logarithm Function : If logx y = logy z = logz x, prove that x = y = z Solution to Solved Example 1 of Logarithm Function : Let logx y = logy z = logz x = K By converting from Logarithmic Form to Exponential Form (See Formula 1), we get xK = y........(i) yK = z.............(ii) zK = x.............(iii) Using the value of y from (i) in (ii), we get z = yK = (xK)K = xK x K = xK2.....(iv) Using the value of x from (iii) in (iv), we get z = xK2 = (zK)K2 = zK x K2 = zK3 Thus we have z1 = zK3 Since the bases are equal, the exponents have to be equal. ? K3 = 1 ? K = 1 Using the value of K in (i) and (ii), we get x1 = y and y1 = z. ? x = y = z (Proved.) Solved Example 2 of Logarithm Function : If (log x)/(b - c) = (log y)/(c - a) = (log z)/(a - b), then prove that xyz = xaybzc = x(b + c)y(c + a)z(a + b) = 1 Solution to Solved Example 2 of Logarithm Function : Let (log x)/(b - c) = (log y)/(c - a) = (log z)/(a - b) = K ? log x = K(b - c); log y = K(c - a); log z = K(a - b); Let the base of the logarithms be p.

log (x2 + xy + y2) = log (a + b) + log (a2 .b) = p{Ka(b .c). (a + b) to x. Ans. Similarly.y) + log (x2 + xy + y2)} We know.{log (x .a) x pK(a .y) . c to x. Solution to 1(ii) of Solving Logarithms : Let P = log (a + b) + log (a2 . (Proved. Cons idering the reverse. y(c + a) = pK(c2 .b)}(1/2). it becomes exponent. logp y = K(c .b) We know in log of a power (see Formula 7) .c) + Kb(c .a + a .a)pKc(a .b) = z. ? P = log {(a + b)(1/2)} .ba + ca .a2) and z(a + b) = pK(a2 .c)}(b + c) = pK(b + c)(b .a) = y.(Proved.ab + b2) .b) (ii) log (a + b) + log (a2 . (Proved. the difference of the logs of different quantitiescan b e written as log of a quotient (the quantity whose log has negative sign.c2) + K(c2 .ac + bc .c). Similarly.log (x .b) By converting from logarithmic form to exponential form (See Formula 1). z respectively.c2)pK(c2 .) We have pK(b .c2). b.(1/2) log (a .b) = p{K(b . we get pK(b . in the denominator) of the quantities.c2 + c2 . the exponent multipliesthe log.b)} = p{K(b . log of a product can be written as the sum of the logs of the factors o .a) = y. pK(c . z respectively.b)} = p{K(0)} = p0 = 1. pK(a . ? xyz = pK(b .) Raising the powers (b + c).c) = x. (c + a).Then the above three equations become logp x = K(b .a) + Kc(a . we get xa = (pK(b .a2) + K(a2 .b2) = pK(0) = p0 = 1.log (x2 + xy + y2) (iii) (3/2) log x .ab + b2) .b2) = pK(b2 .) Example 1 of Solving Logarithms : Express the following as single logarithms to any base.c) x pK(c .log (x .c)pKb(c . we get x(b + c) = {pK(b .a). y.(1/2) log (a . pK(a .a2)pK(a2 . (i) (1/2) log (a + b) .ab + b2) . If a quantity multiplies thelog. yb = pKb(c .cb} = pK{0} = p0 = 1.b)} = pK{ab .b) Multiplying these three. pK(c . we get xaybzc = pKa(b .b2) = pK(b2 . y.(1/5) log a Solution to Example 1 of Solving Logarithms : Solution to 1(i) of Solving Logarithms : Let P = (1/2) log (a + b) .log {(a .c) = x.a) and zc = pKc(a .y) . we get x(b + c)y(c + a)z(a + b) = pK(b2 .c + c . logp z = K(a .b)(1/2)} = log {(a + b)/(a .a2 + a2 .b)(1/2)} We know.c) + K(c .c) = pK(b2 .a) + K(a . = log {(a + b)(1/2)}/{(a .b) = z.b2) Multiplying these three. Raising the powers a.c))a = pKa(b .(1/3) log y + (2/3) log z . log of a quotient can be written as the difference of the logs of the numerator and denominator of the qu otient (See Formula 6) Considering the reverse.

it becomes exponent. the sum of the logs of different quantitiescan be writt en as log of product of the quantities. in the denominator) of the quantities.log 3 + log 4 We know in log of a power (see Formula 7) .log {(x . Example 2 of Solving Logarithms : Solve the equations (i) 3(2x + 1).1) log 4 = log 36 ? 2x log 3 + 4x log 4 + log 3 . log of a product can be written as the sum of the logs of the factors o f the product (See Formula 5) Considering the reverse. the exponent multipliesthe log. the exponent multipliesthe log.ab + b2)} . = 2x(log 3 + log 42) We know. the sum of the logs of different quantitiescan be writt en as log of product of the quantities.log 4 = log 36 ? 2x(log 3 + 2 log 4) = log 36 .y)(x2 + xy + y2)} We know from Polynomials.1) = 36 Taking logarithms on both sides.f the product (See Formula 5) Considering the reverse. the sum of the logs of different quantitiescan be writt en as log of product of the quantities. in the denominator) of the quantities. the difference of the logs of different quantitiescan b e written as log of a quotient (the quantity whose log has negative sign. we get log {3(2x + 1).{log y(1/3) + log a(1/5)} We know. ? P = log {(a + b)(a2 .4(4x .4(4x . log of a quotient can be written as the difference of the logs of the n umerator and denominator of the quotient (See Formula 6) .y3) We know. Solution to 1(iii) of Solving Logarithms : Let P = (3/2) log x . and (x . ? P= log {(a3 + b3)/(x3 .1)} = log 36 We know in log of a power (see Formula 7) . Cons idering the reverse. ? P = log [{x(3/2) x z(2/3)}/{y(1/3) x a(1/5)}] Ans.S.H.y3 ? P = log (a3 + b3) . Cons idering the reverse.ab + b2) = a3 + b3. it becomes exponent. ? (2x + 1) log 3 + (4x .1) = 36 (ii) 4(log9 3) + 9(log2 4) = 10(logx 83) Solution to Example 2 of Solving Logarithms : Solution to 2(i) of Solving Logarithms : 3(2x + 1).(1/5) log a We know in log of a power (see Formula 7) .1)} = log 36 ? log {3(2x + 1)} + log {4(4x . the exponent multipliesthe log.4(4x . log of a quotient can be written as the difference of the logs of the n umerator and denominator of the quotient (See Formula 6) Considering the reverse. log of a quotient can be written as the difference of the logs of the n umerator and denominator of the quotient (See Formula 6) Considering the reverse. We know. If a quantity multiplies thelog.(1/3) log y + (2/3) log z . the difference of the logs of different quantitiescan b e written as log of a quotient (the quantity whose log has negative sign. ? P = log {x(3/2) x z(2/3)} .log (x3 . ? P = log x(3/2) + log z(2/3) .log {y(1/3) x a(1/5)} We know.y)(x2 + xy + y2) = x3 . If a quantity multiplies thelog. ? L. (a + b)(a2 . log of a product can be written as the sum of the logs of the factors o f the product (See Formula 5) Considering the reverse.y3)} Ans.

? x = 10. ? log2 4 = 2 log2 2 We know log of a quantity to the same base is 1. the difference of the logs of different quantitiescan b e written as log of a quotient (the quantity whose log has negative sign.H. .(42)2x..S. in log of a power (See Formula 7). to conclude x = 10. Ans.the quot ient of the exponents (exponent of the base in the denominator) multiplies the l og.. Ans. log of a quantity to a base can be written asthe ratio of log of the qu antity and log of the base.(3/4) = 36 ? 32x... w e get logx 83 = log10 83 When two logarithms of same quantities are equal. (See Formula 4) ? log2 4 = 2 (1) = 2 ? the given equation becomes 4(1/2) + 92 = 10(logx 83) ? 2 + 81 = 10(logx 83) ? 83 = 10(logx 83) . the exponent multiplies the log. the exponent multipliesthe log. Alternative Solution: This problem can be solved from Exponents knowledge withou t using logarithms as given below. the exponent multiplies the log.4(4x .S.. in the denominator) of the quantities.1) = 36 ? 3(2x).(See Formula 8) ? a = 3 {(log 3)/(log 12)} We know 12 = 3 x 4 = 3 x 22 ? log 12 = log (3 x 22) We know. ? log9 3 = (1/2) log3 3 We know log of a quantity to the same base is 1. log of a product is equal to the sum of the logs of the factors of the product (See Formula 5) ? log 12 = log 3 + log (22) We know. in log of a power (See Formula 7). 3(2x + 1).(i) By converting the exponential form of (i) to logarithmic form (See Formula 1).4(-1) = 36 ? (3)2x. ? a = 3 log12 3 We know. their bases have to be equal. Solution to 2(ii) of Solving Logarithms : The given equation is 4(log9 3) + 9(log2 4) = 10(logx 83) We have log9 3 = log32 31 We know.31. find log30 8 Solution to Example 1 of Common Logarithms : Solution to 1(i) of Common Logarithms : If log12 27 = a. we get 2x{log (3 x 42)} = log (36 x 4/3) = log 48 ? 2x{log 48} = log 48 ? 2x = 1 ? x = 1/2.4(4x). You can also apply Formula 2 to equation (i). Solved Example 1 of Common Logarithms : (i) If log12 27 = a..Considering the reverse.H. Ans.. in log of a power to the base of another power (see Formula 9). and R.Ans. (See Formula 4) ? log9 3 = (1/2) (1) = 1/2. log2 4 = log2 22 We know in log of a power (see Formula 7) .(16)2x = 36 x (4/3) = 48 ? (3 x 16)2x = 48 ? (48)2x = 48 ? 2x = 1 ? x = 1/2. compute log6 32 in terms of a (ii) If log30 3 = a and If log30 5 = b. Applying these to L. compute log6 32 We have a = log12 27 = log12 33 We know.

.logn b) We know.. in log of a power (See Formula 7).a)/2a .. ? x = {log (25}/{log (2 x 3)} Numerator is logarithm of a power and Denominator is logarithm of a product.x)/(xy)} x {(yz)/(z . 1/z = logc n To prove (loga n)/(logc n) = {(loga n) .a)/2a ...a + 2a)/2a = (3 + a)/2a.S. log30 30 = 1 ? log30 30 = 1 ? log30 (3 x 5 x 2) = 1 We know.H. the reciprocal of the log of a quantity to a base is equal to the log w ith the quantity and the base interchanged.a)/2a + 1 = (3 .... we get x = 5 {(3 .H. log of a quantity to a base can be written asthe ratio of log of the qu antity and log of the base. prove that (loga n)/(logc n) = {(loga n) .b log30 8 = log30 (23) We know. = (loga n)/(logc n) = (1/x)/(1/z) = z/x ..x)/(xy)}/{(z .(logb n)}/{(logb n) . We know. in log of a power (See Formula 7)..(ii) Substituting the value of p from (i) and (p + 1) from (ii) in x.. log of a product is equal to the sum of the logs of the factors of the product (See Formula 5) ? log30 3 + log30 5 + log30 2 = 1 ? a + b + log30 2 = 1 ? log30 2 = 1 ..(ii) R..(i) ? p + 1 = (3 . log of a quotient can be written as the difference of the logs of the n umerator and denominator of the quotient (See Formula 6) .y)} = (z/x){(y ....(i) Let x = log6 32 We know.(logc n)} = {(1/x) . Let y = logn b then 1/y = 1/logn b.y)}.. We know... If b = v(ac)....b)..(1/y)}/{(1/y) . Let z = logn c then 1/z = 1/logn c.. Ans. 6 = 2 x 3.....(logb n)}/{(logb n) .a)/a ? p = (3 . 1/y = logb n..S. the exponent multiplies the log. we get x = 5 (log 2/log 3)/{(log 2/log 3) + 1} = 5p/(p + 1) [Since p = (log 2/log 3)] We have p = (3 ..(logb n)}/{(logb n) .(See Formula 8) ? x = (log 32)/(log 6) We know 32 = 2 x 2 x 2 x 2 x 2 = 25.a)/2a}/{(3 + a)/2a} = 5 {(3 ....(iii) (y . ? log30 8 = 3(log30 2) = 3(1 .a . Solution to 1(ii) of Common Logarithms : we know 30 = 3 x 5 x 2..logn a)/(logn c ..(See Formula 10) ? 1/x = loga n...? log (22) = 2 log 2 Thus log 12 = log 3 + 2 log 2 ? a = 3 {(log 3)/(log 3 + 2 log 2 )} Dividing numerator and denominator by log 3..a ..1 = (3 . = {(loga n) .(1/z)} = {(y ..(logc n)} L... Ans....(logc n)} Solution to Example 2 of Common Logarithms : By data b = v(ac) ? b2 = ac ? b/a = c/b.x)/(z .x)/(z .(i) Let x = logn a then 1/x = 1/logn a... we get a = 3 [(1)/{1 + 2 (log 2/log 3)}] = 3/(1 + 2p) where p = (log 2/log 3) ? 1 + 2p = 3/a ? 2p = 3/a .a)/(3 + a)}. log of a product is equal to the sum of the logs of the factors of the product (See Formula 5) ? x = {5 log 2}/{log 2 + log 3} Dividing numerator and denominator by log 3.y)/(yz)} = {(y . We know.y) = (logn b . the exponent multiplies the log..

S. You can use the word 'Similarly' and write Equations (ii) and (iii) directly. we get ax = bc Multiplying both sides with a. we get .S. Reciprocal of R. we get b x by = b x ca ? by + 1 = bca = abc By converting from Exponential Form to Logarithmic Form (See Formula 1). = logabc a ? 1/(x + 1) = logabc a. in the denominator) of the quantities. Solution to Example 1 of Natural Logarithms : By data. = 1/(x + 1).H. the reciprocal of the log of a quantity to a base is equal to the log w ith the quantity and the base interchanged. we get Reciprocal of L. we get x + 1 = loga abc Taking reciprocals.(See Formula 10) ? Reciprocal of R..y) = {logn (b/a)}/{logn (c/b)} = 1 [Since b/a = c/b from (i)] Using this value in (iii).Considering the reverse. logc ab = z By converting from logarithmic cz = ab Multiplying both sides with c. logb ca = y.H. the reciprocal of the log of a quantity to a base is equal to the log w ith the quantity and the base interchanged..) Thus Example 2 of Common Logarithms is solved. (Proved.H.x)/(z . L..H.S.H.H.H. By data..H.. = 1/(loga abc) We know.. we get a x ax = a x bc ? ax + 1 = abc By converting from Exponential Form to Logarithmic Form (See Formula 1)..S. ? (y . then prove that 1/(x + 1) + 1/(y + 1) + 1/(z + 1) = 1.Two more repetitions of th e Application ofFormula 1 (both ways) and Formula 10 will help you rememberthem.. If loga bc = x. the difference of the logs of different quantitiescan b e written as log of a quotient (the quantity whose log has negative sign. = R. But I am givingbelow the repititions. we get we get = abc Form to Logarithmic Form (See Formula 1). c x cz = c x ab ? cz + 1 =ca b By converting from Exponential z + 1 = logc abc Taking reciprocals. = (z/x) (1) = z/x From (ii).(ii) By data. logc ab = z.S. we get R.S.H. = z/x ? L. = 1/(y + 1) Reciprocal of R. loga bc = x By converting from Logarithmic Form to Exponential Form (See Formula 1). we get Reciprocal of L. we get by = ca Multiplying both sides with b. = logabc b ? 1/(y + 1) = logabc b .S...(i) Next two paragraphs are repetition of the procedure in the above paragraph with variables changed.S. logb ca = y By converting from logarithmic form to exponential form (See Formula 1).. we get y + 1 = logb abc Taking reciprocals..S.H.(See Formula 10) ? Reciprocal of R. we get form to exponential form (See Formula 1).S. = 1/(logb abc) We know.

H.S. = 1 + xyz = 1 + (log a)/(log 4a) = {(log 4a) + (log a)}/(log 4a) We know.the quot ient of the exponents (exponent of the base in the denominator) multiplies the l og.H.S.. log of a quantity to a base can be written asthe ratio of log of the qu antity and log of the base. the ratio of logs of two quantities can be written as a single log with the denominator quantity as base. = {2 log (2a)}/(log 4a) R.. = logabc c ? 1/(z + 1) = logabc c .) If x = log 2a a.(iii) (i) + (ii) + (iii) gives 1/(x + 1) + 1/(y + 1) + 1/(z + 1) = logabc a + logabc b + logabc c = logabc abc We know log of a quantity to the same base is 1.H. the sum of the logs of different quantitiescan be writt en as log of product of the quantities.) Find the value of (i) log343 49 (ii) log0.S. ? L.H. .. ? L. in log of a power (See Formula 7).. y = log 3a 2a. = R.Reciprocal of L.S. then prove that 1 + xyz = 2yz Solution to Example 2 of Natural Logarithms : We know.H.(See Formula 8) Considering the reverse.S.0001) (iii) log(2v3) (1728) Solution to Example 1 of Solving Algebra Problems : (i) Let A = log343 49 We know 49 = 7 x 7 = 72.(See Formula 8) x = log 2a a = (log a)/(log 2a) y = log 3a 2a = (log 2a)/(log 3a) z = log 4a 3a = (log 3a)/(log 4a) xyz = {(log a)/(log 2a)}{(log 2a)/(log 3a)}{(log 3a)/(log 4a)} = (log a)/(log 4a) We know. z = log 4a 3a.S.. ? xyz = log 4a a Now to prove 1 + xyz = 2yz L. (proved. log of a quantity to a base can be written asthe ratio of log of the qu antity and log of the base.H..H.H. = 1/(logc abc) We know. (proved. the reciprocal of the log of a quantity to a base is equal to the log w ith the quantity and the base interchanged. = 2yz = 2 {(log 2a)/(log 3a)}{(log 3a)/(log 4a)} = 2 (log 2a)/(log 4a) ? L.S.(See Formula 10) ? Reciprocal of R.H. = {log (4a x a)}/(log 4a) = {log (4a2)}/(log 4a) = {log (4a2)}/(log 4a) = {log (2a)2}/(log 4a) We know. ? A = (2/3) log7 7 But log of any number to the same Base is one (see Formula 4). = 1/(z + 1) Reciprocal of R. the exponent multiplies the log. (See Formula 4) ? 1/(x + 1) + 1/(y + 1) + 1/(z + 1) = 1.S.01 (0. 343 = 49 x 7 = 7 x 7 x 7 = 73 ? A = log343 49 = log(73) (72) We know. log of a product can be written as the sum of the logs of the factors o f the product (See Formula 5) Considering the reverse.S. in log of a power to the base of another power (See Formula 9).

H.H. we get x = log(2.log1000 (0. in log of a power (see Formula 7).3) 1000) We know.23) We know.? A = (2/3) (1) = 2/3.H.01 x 0. (ii) Let A = log0.H.23)} = log1000 (10) = log103 (101) We know.(See Formula 10) ? Reciprocal of R. If (2.01) (0. ? A = log(2v3) (1728) = log{12(1/2)} (123) We know. in the denominator) of the quantities.(See Formula 10) ? Reciprocal of R.01 = (0. = 1/x . = 1/(log(2. = log1000 {(2.H. we get y = log(0.23) ? 1/y = log1000 (0. ? A = {3/(1/2)} log12 12 But log of any number to the same Base is one (see Formula 4). the reciprocal of the log of a quantity to a base is equal to the log w ith the quantity and the base interchanged. = 1/x Reciprocal of R. ? A = log(0.3) By data (0. show that 1/x .01)2} We know.S. ? A = 2 (1) = 2.S.3) 1000 Taking reciprocals.01) But log of any number to the same Base is one (see Formula 4).S. ? L. = 1/(log(0.23) 1000) We know.01) {(0.1/y = 1/3 Solution to Example 2 of Solving Algebra Problems : By data (2.3)x = (0.23)y = 1000 By converting from Exponential Form to Logarithmic Form (See Formula 1). = log1000 (0. ? A = 2 log(0. = 1/y Reciprocal of R. = log1000 (2. we get Reciprocal of L. (iii) Let A = log(2v3) (1728) We know 2v3 = 2 x (3)(1/2) = (22)(1/2) x (3)(1/2) = 4(1/2) x (3)(1/2) = (4 x 3)(1/2) = 12(1/2) 1728 = 12 x 144 = 12 x 12 x 12 = 123 See how the base (2v3) and 1728 are made as powers of the same number 12.S.3)/(0. in log of a power to the base of another power (see Formula 9). we get Reciprocal of L. the difference of the logs of different quantitiescan b e written as log of a quotient (the quantity whose log has negative sign.3) .23) 1000 Taking reciprocals. the reciprocal of the log of a quantity to a base is equal to the log w ith the quantity and the base interchanged. in log of a power to the base of another power (see Formula 9).0001) = log(0.3) ? 1/x = log1000 (2. ? A = (3 x 2) (1) = 6. Ans.the quot .1/y = 1/3 L.1/y = log1000 (2. the exponent multiplies the log. Ans.0001) We know 0.S.01)2. Ans.H.H.H.the quot ient of the exponents (exponent of the base in the denominator) multiplies the l og.3)x = 1000 By converting from Exponential Form to Logarithmic Form (See Formula 1). Thus log(2v3) (1728) = 6.S.23)y = 1000.01) (0.01 (0.0001 = 0.S. log of a quotient can be written as the difference of the log of the nu merator and denominator of the quotient (See Formula 6) Considering the reverse.S.23) To prove 1/x .

(See Formula 4) ? L.S.H.S.ient of the exponents (exponent of the base in the denominator) multiplies the l og.S.H.H. = (1/3) (1) = 1/3 = R. = (1/3) log10 10 We know log of a quantity to the same base is 1. ? L. (Proved.) .